Mycobacterium bovis vaccination and subsequent experimental infection outcomes are associated with changes in vitamin D status in dairy calves - Rachel L. Lee; Kieran G. Meade; Shelley G. Rhodes; Tom Ford; Ilias Kyriazakis (JDS Communications)
Investigations into the role of vitamin D (vitD) in the immune response of cattle are limited. The objectives of this study were therefore to investigate the association between circulating vitD concentration, tuberculosis (TB) vaccination, and Mycobacterium bovis infection outcomes in 24 dairy calves (<8 wk old) that were housed throughout and fed a BW-based allowance. The study design incorporated 2 phases: vaccination (experimental wk 0–52) and experimental infection phase (wk 52–65). Vaccinated calves (n = 12) received a subcutaneous injection of a live attenuated TB strain at wk 0, whereas unvaccinated ones (n = 12) were injected with saline. All animals were infected with 7,600 cfu of M. bovis 52 wk postvaccination, and lung and lymph node tissues were assessed for pathology following euthanasia after wk 65. Blood samples were taken throughout wk 0 to 65. Serum 25-hydroxyvitamin D [25(OH)D] concentrations were measured using a commercial ELISA. A mixed-effects linear regression model revealed significantly higher 25(OH)D concentrations in the vaccinates postinfection (wk 65) compared with the nonvaccinates. Linear regression analysis between 25(OH)D concentration and the level of M. bovis-driven pathology revealed a negative linear relationship (i.e., higher concentrations were associated with lower pathology scores) irrespective of vaccination status. No correlation was detected between IFN-γ cytokine production and vitD concentration. Overall, the results support an impactful role for vitD in the development of effective immunity of cattle against M. bovis. Gaining insight into the interaction between TB vaccination, M. bovis infection, and vitD could potentially guide the optimization of vaccination protocols and future TB control strategies.